[updated from 2017] Vicious Worm training app for cysticercosis control - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
Tool developed and made available on the app store and disseminated to sub-national levels through focus groups. Translated to Swahili and Kinyarwanda